A facile and practical p-toluenesulfonic acid catalyzed route to dicoumarols and their biological evaluation. Issue 1 (2nd January 2023) - Al-Hazmy, Sadeq M.; Bensalah, Donia; Dlala, Najet Aouled; Bouazizi, Younes; Ghalla, Houcine; Hamdi, Naceur
ABSTRACT: New Dicoumarols 2a-g efficiently synthesized employing p-TSA as a catalyst from the reaction of 4-hydroxycoumarin with aryl aldehydes in water. This method offers direct access to structurally diverse Dicoumarols derivatives in a good yields (65-94%). Upon heating 3, 3' -arylidenebis-4-hydroxycoumarins derivative in acetic anhydride, the epoxydicoumarins were formed. 1H, 13C{1H}-NMR, elemental analysis, and infrared spectroscopic techniques were used for the characterization of the obtained compounds. A possible relationship between such hydrogen-bonded structures and the antimicrobial and the antioxidant activities of compounds is suggested. The synthetized compounds 2a-g and 3a-g were subjected to in vitro antimicrobial and antifungal activities against DNA gyrase and Mycobacterium tuberculosis-CYP51 target proteins at the active sites. Compound 3d shows effective inhibitory effect in terms of MIC = 15 µg mL-1. against Salmonella typhimuriumATCC 14028. Compounds 2b, 2c, 3b, 3c, 3e and 3g have recorded an important scavenging activity against the radical DPPH. The EC50 of these compounds was 47.17, 46.90, 50.55, 48.27, 46.55 and 47.54 µg mL-1 respectively. Investigation of the anti-inflammatory activity of the synthesized compounds showed that compounds 2b, 2c, 3f, 3b and 3c are the most potent inflammatory activities. GRAPHICAL ABSTRACT: UF0001